2007
DOI: 10.1016/j.cell.2007.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Challenges during DNA Replication and Repair

Abstract: Inheritance and maintenance of the DNA sequence and its organization into chromatin are central for eukaryotic life. To orchestrate DNA-replication and -repair processes in the context of chromatin is a challenge, both in terms of accessibility and maintenance of chromatin organization. To meet the challenge of maintenance, cells have evolved efficient nucleosome-assembly pathways and chromatin-maturation mechanisms that reproduce chromatin organization in the wake of DNA replication and repair. The aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
574
0
4

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 674 publications
(592 citation statements)
references
References 116 publications
6
574
0
4
Order By: Relevance
“…DNA repair is no exception, and dynamic changes in chromatin condensation and accompanying histone marks have been recognized as inevitable DDR pathways [15,[75][76][77][78][79][80]. Here, too, the DDR relies on recruitment of existing players in the chromatin organization arena [32][33][34][75][76][77][78][79][81][82][83][84][85].…”
Section: Rnf20-rnf40 Is Called To Emergency Action Upon Dna Damage Inmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA repair is no exception, and dynamic changes in chromatin condensation and accompanying histone marks have been recognized as inevitable DDR pathways [15,[75][76][77][78][79][80]. Here, too, the DDR relies on recruitment of existing players in the chromatin organization arena [32][33][34][75][76][77][78][79][81][82][83][84][85].…”
Section: Rnf20-rnf40 Is Called To Emergency Action Upon Dna Damage Inmentioning
confidence: 99%
“…Information about the interface between the DDR and chromatin organization is rapidly accumulating [75,76,78,108,[118][119][120]]. An early, extremely rapid process at damage sites is the CK2-mediated phosphorylation and eviction of the heterochromatin protein 1 (HP1) [121].…”
Section: Rnf20-rnf40 Is Called To Emergency Action Upon Dna Damage Inmentioning
confidence: 99%
See 1 more Smart Citation
“…This dynamic nature has been confirmed by more recent cell and molecular studies. First, essential processes, such as gene transcription, DNA replication and repair, all involve disruption and reassembly of chromatin structure [9,10]. Second, Fluorescence recovery after photobleaching (FRAP) studies have shown that most chromatin-bound proteins are not statically bound, but exhibit relatively high "off" and "on" rates, even in supposedly "closed" heterochromatin [11,12].…”
Section: The Dynamic and Stochastic Properties Of Chromatinmentioning
confidence: 99%
“…Another scenario could be that the hMOFdepleted cells may have a defective S phase checkpoint, therefore leading to the observed G 2 /M accumulation. We can speculate that a hMOF-dependent reduction of H4K16 acetylation, a modification that reaches its highest levels during mid-S phase (Rice et al, 2002), could affect DNA replication, as during this phase a tight co-ordination between DNA replication and preservation of epigenetic integrity must be achieved (Groth et al, 2007). An alternative explanation would be that loss of hMOF could impair the cell's ability to repair DNA, thereby activating the G 2 /M checkpoint.…”
Section: Hmof In the Dna Damage Responsementioning
confidence: 99%